Never-more : the final Maximum Ride adventure - Patterson, James, 1947- (New York, NY : Little, Brown and Co. [Scholastic], 2012)
One last chance for Max, Fang, and Dylan before it all ends. "Nevermore" is one last incredible, explosive adventure with an astonishing ending that no one could have seen coming.
Keywords: Friendship -- Fiction; Magic -- Fiction; Genetic engineering -- Fiction; Suspense fiction; Adventure stories; Science fiction; Young adult fiction; Suspense fiction; Adventure fiction; Science fiction; Young adult fiction